신명기 관점에서 본 반(反)다문화 담론 속 타자 배제의 대응방안 ‐ 신명기 게르 텍스트 분석을 통해 - 김영선(KIM Young-Seon) (Changsin nondan, 2024)
반다문화 담론 속 문화 근본주의는 이주자들의 문화의 차이들을 배제의 기제로 사용함으로써 본질적으로 인종 차별적인 태도와 정책을 채택하고 있다. 신명기 게르 텍스트들 속 포용의 원리는 그러한 인종주의를 해결하는 하나의 대안이 될 수 있다. 신명기에서 게르의 사회적 포용은 다양한 규정들의 상호 작용을 통해 달성되는데, 사회법은 게르의 착취를 방지하며, 게르 또한 풍요로운 토지산물의 핵심 수혜자임을 명시한다. 재판의 법은 게르에 대한 사법적 정의를 보장하고 이들의 완전한 경제적, 사회적 참여의 가능성을 열어준다. 절기의 법은 게르를 가족과 씨족 내에 통합시킨다. 신명기의 급진적 환영 윤리는 오늘날 선교적 공동체가 나아갈 방향을 지시하는데, 이는 반다문화 담론에서 나타나는 이주자 및 취약한 자들에 대한 배제를 비판하고, 가정과 지역사회 차원에서 그들과의 유대를 강조하고, 불평등을 완화시키며, 궁극적으로 그들을 포용하는 대안적 공동체, 즉 선교적 공동체의 형성을 촉구한다. Cultural fundamentalism in anti-multicultural discourses promotes racism by using immigrants cultural differences as a means of exclusion. The principle of inclusion found in the ger texts of Deuteronomy offers an alternative to such discrimination. In Deuteronomy, various regulations work together to ensure the social inclusion of the ger: social laws protect them from exploitation and guarantee their share of the lands abundance. Judicial laws secure their legal rights and enable their full participation in economic and social life. Festival laws integrate them into family and clan structures. This radical ethic of hospitality in Deuteronomy guides todays missional communities, calling them to challenge the exclusion of immigrants and vulnerable people, strengthen bonds at household and community levels, reduce inequalities, and ultimately build an alternative, inclusive community—a missional community. KCI Citation Count: 0